Photoacclimation to Constant and Changing Light Conditions in a Benthic Diatom - Pniewski, Filip; Piasecka-Jędrzejak, Iwona (Frontiers in Marine Science, 2020)
ABSTRACT Photoacclimation to constant and changing light conditions was studied in the benthic diatom Nitzschia cf. aurariae isolated from the littoral zone of the Baltic Sea. The diatom was grown under a wide range of irradiances, i.e., 15-350 mol photons m-2 s-1 with the photoperiod of 16h of light and 8h of darkness. In the first experiment, three levels of a constant light were applied, i.e. 30, 115 and 350 mol photons m-2 s-1. In the second experiment, the diatom was exposed to two ranges of changing light conditions, i.e., the lower-range of variable light, i.e., 15-30-150 mol photons m-2 s-1, and the higher-range of variable light, i.e., 30-60-350 mol photons m-2 s-1. The cellular content of photosynthetic (chlorophyll a and fucoxanthin), as well as photoprotective pigments (diadinoxanthin and diatoxanthin), was determined by the total daily light doses. The de-epoxidation state of the xanthophyll cycle reached higher values in cultures maintained under variable light regimes. The analysis of photosynthesis-irradiance curves suggested that N. cf. aurariae acclimated primarily through the changes in the number of photosynthetic units (PSU). Higher photosynthetic rates observed under variable irradiance indicated the maximization of photosynthesis at lower light intensities. In constant high light, the diatom accumulated more photoprotective pigments, however, the activity of the xanthophyll cycle was limited. Under variable light regimes wide changes in the de-epoxidation state allowed for efficient photoprotection, depending on the light intensities applied. Photoprotection appeared to represent an interplay between long-term photoacclimation and rapid adjustment to ambient light conditions within the constraints set by the former. Prolonged exposure to high light caused a decrease in photosynthetic rates. However, the stable growth of the diatom across the applied light intensities showed that it can survive periods of potentially stressful light conditions. Acclimation mechanisms observed in the studied diatom were consistent with those observed in microalgae present in habitats characterized by high irradiance and rapid changes in light conditions.